UJI AKTIVITAS ANTIBAKTERI MADU HUTAN TERHADAP BAKTERI Bacillus cereus - Maimunah, Siti; Supartiningsih, Supartiningsih; Marpaung, Jon Kenedy; Silalahi, Yosy Cinthya Eriwaty; Turnip, Icha Wahyuni (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Honey is a thick sweet liquid which comes from bees which can cure many diseases and is antibacterial. Antibacterial potential of honey caused by the content of active compounds, low moisture content, high osmolarity, hydrogen peroxide content, and low pH.The aim of this study was to determine the antibacterial activity of forest honey on Doloksaribu, Simalungun district on the growth of Bacillus cereus bacteria.Experiment research method includes the analysis quality of honey, includes checking moisture content, ash content, pH tested, acidity, viscosity, spesific gravityphytochemical screening, and antibacterial activity test ith disk diffusion method use blank disk with each concentration 25%, 35%, 45%, 55%, and 65%, positive control using erythromycin and negative control sterile distilled water. Organoleptic test conducted on forest honey gave results that honey reach the requirements for good quality. The result of moisture and ash content test and pH test reach of SNI 3545: 2013 about honey. Antibacterial activity test of forest honey with concentration 25%, 35%, 45%, 55%, and 65% against Bacillus cereus showed that there was an inhibitory around the blank disc, namely 10,16 mm, 13 mm, 15,6 mm, 21,6 mm, and 22,6 mm. The greatest inhibition of forest honey occurred at the highest concentration that is 65% (22,6 mm).